(untitled) (The Pakistan Development Review, 2007)
The country’s geographical area is 79.61 million hectares (mha), excluding the Northern Areas of Pakistan. Out of this, only 72 percent area has been reported indicating a major limitation that 28 percent area is not yet surveyed for land use classification. The reported area is further classified into four major classes: (a) forest area of 4.02 mha; (b) area not available for cultivation of 22.88 mha; (c) culturable waste of 8.12 mha; and (d) cultivated area of 22.05 mha. Out of the reported area, around 8.1 mha are available for future agriculture and other uses, if water is made available. If rest of the area (28 percent) is also surveyed then one can have better picture of country’s land resources (Table 1).